STRATEGI FACT-CHECKING REDAKSI ANTARA TV PADA PRODUKSI BERITA PEMERINTAHAN DAN KEBIJAKAN PUBLIK - Desna Aryana; Nabilla Regita Khairani; Rizky Wulan Ramadhani; Sabrina Rahma Utami (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2026)
The development of digital media increases the risk of spreading misinformation and disinformation. The increase in disinformation has pushed fact-checking to become an important practice in contemporary journalism. ANTARA TV is one of the television media that conducts fact-checking to verify the facts of its news reports in order to become a credible media for the public. The purpose of this study is to determine the fact-checking strategy implemented by the ANTARA TV editorial team in the process of producing government and public policy news. This study uses a qualitative method with a case study approach through interviews with the head of the video department, producers, reporters, editors, and viewers of ANTARA TV. In addition, researchers also conducted observations of the ANTARA TV news production process and documentation. Researchers used the Gatekeeping Theory from Shoemaker & Reese and Shoemaker & Vos to analyze the fact-checking strategy implemented by ANTARA TV. The results show that the ANTARA TV editorial team implements a fact-checking strategy through a multi-level gatekeeping mechanism, namely the individual level, the editorial routine level, and the organizational level. Multi-level gatekeeping is implemented through the development of editorial work procedures, multiple verifications of official documents, confirmation with credible sources, and the use of internal guidelines to simplify technical policy terms for easier audience understanding. The implementation of fact-checking contributes to minimizing misinformation, improving reporting accuracy, and strengthening public trust in ANTARA TV as a media outlet that responsibly produces government and public policy news.